(untitled) (Revista de Ciências Agroveterinárias, 2007)
This study was carried out aiming to evaluate the field performance of a Prentice Blount feller-buncher model Hydro AX-611E, according to time and motion observed in wood felling work. The research evaluated harvesting operations including cutting, bunching, felling and reducing stumps height of a six-year-old Eucalyptus saligna smith forest. The methodology used was based on the determination of machine time and movement during commercial harvesting and its respective full-tree wood production. The eucalyptus harvester’s whole production cycle had a mean duration of 60.02 +/- 13.11 seconds, resulting in a mean production of 4.41 +/- 0.90 full-trees. There was no functional association between the harvesting operation time and the number of harvested tress. This result showed that several factors affected the harvesting process, such as the field work conditions, type of forest, harvesting machine and machine operator.